1972
DOI: 10.1111/j.1432-1033.1972.tb01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple Computer-Aided Approach for the Analyses of the Nuclear-Magnetic-Resonance Spectra of Histones. Fractions Fl, F2al, F2B, Cleaved Halves of F2B and F2B middotDNA

Abstract: A simple method for the computer simulation of high-resolution nuclear magnetic resonance spectra is described and applied to the analyses of salt-induced changes in the spectra of histones. The method is more objective than the earlier approach of visual examination of spectral changes.It allows the information contained in the spectral envelope to be used and has led to some modifications of the earlier proposals of the segments of histones involved in salt-induced conformational changes, interhistone intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2

Year Published

1975
1975
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 25 publications
6
37
2
Order By: Relevance
“…The percentage and location of ordered protein found in the new map also correlate well with the findings of Bradbury and coworkers (23)(24)(25), who reported that residues 25-95 of H2A, 37-114 of H2B, 42-110 of H3, and 33-102 of H4 are ordered. Our model includes these residues and extends the structured portion of the octamer by 66 more residues (Fig.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The percentage and location of ordered protein found in the new map also correlate well with the findings of Bradbury and coworkers (23)(24)(25), who reported that residues 25-95 of H2A, 37-114 of H2B, 42-110 of H3, and 33-102 of H4 are ordered. Our model includes these residues and extends the structured portion of the octamer by 66 more residues (Fig.…”
Section: Methodssupporting
confidence: 88%
“…2). This is slightly in excess of the 62% assigned to structured residues by the earlier studies of Bradbury and associates (23)(24)(25). Within the perspective of viewing this assembly, three distinct shapes can be perceived and the overall mass distribution can be described as tripartite or tetrapartite.…”
Section: Methodsmentioning
confidence: 72%
“…This is in contrast to the view expressed by Rattle (1972) andIsenberg (1974a,b), where histone molecules are regarded as completely random coil molecules in the absence of salt.…”
Section: Discussionmentioning
confidence: 64%
“…The slow conformattonal exchange localized around the cystems which bmd the two zmc atoms of the protein observation is confirmed by the analysis of the Bl field strength dependence of the Tl relaxation m the rotating frame The measurement of this so called Tlp relaxation time constant was also recently used m the analysts of slow motion m BPTI [25] A further example of disorder m a DNA bmdmg protein, that of the Antennapedia homeodomam, has more recently been described by Qian et al [26] The existence of extensive flexible regions m histones, known since the pioneermg NMR studies of E M Bradbury [27,28], have been discussed by C Cerf [29] 4. The significance of conformational flexibility A possible functional stgmficance for the disorder observed for residues 20-30 of the B-chain of an msuhn mutant was proposed by M Weiss In a series of msulm analogues such disorder can be seen both by NMR and crystallography and its role m facihtatmg a conformational admstment upon receptor bmdmg represents an attractive hypothesis [30] A somewhat different type of bmdmg site flextbihty was described by G.C.K.…”
Section: Slow Conformational Exchangementioning
confidence: 99%